2020
DOI: 10.1103/physrevlett.124.036801
|View full text |Cite|
|
Sign up to set email alerts
|

Nonlocal Conductance Spectroscopy of Andreev Bound States: Symmetry Relations and BCS Charges

Abstract: Two-terminal conductance spectroscopy of superconducting devices is a common tool for probing Andreev and Majorana bound states. Here, we study theoretically a three-terminal setup, with two normal leads coupled to a grounded superconducting terminal. Using a single-electron scattering matrix, we derive the subgap conductance matrix for the normal leads and discuss its symmetries. In particular, we show that the local and the nonlocal elements of the conductance matrix have pairwise identical antisymmetric com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 47 publications
4
92
0
Order By: Relevance
“…The transport within the bulk gap is dominated by the local, Andreev processes, while the main contribution to transport above the bulk gap comes from the nonlocal, direct transmission. The excitation spectrum above the bulk gap contains several series of crossings and avoided crossings, ubiquitous in the spectra of Majorana nanowires [13,15,17,27,[31][32][33]. Our analysis sheds light on the nature of these states' features.…”
Section: Introductionmentioning
confidence: 77%
“…The transport within the bulk gap is dominated by the local, Andreev processes, while the main contribution to transport above the bulk gap comes from the nonlocal, direct transmission. The excitation spectrum above the bulk gap contains several series of crossings and avoided crossings, ubiquitous in the spectra of Majorana nanowires [13,15,17,27,[31][32][33]. Our analysis sheds light on the nature of these states' features.…”
Section: Introductionmentioning
confidence: 77%
“…(a) However, a recent theoretical work showed that the anti-symmetric components of local an nonlocal conductances are related by [30]…”
Section: Finite-bias Nonlocal Conductance In a Three-terminal Geometrymentioning
confidence: 99%
“…This allows to measure local signatures of MBS such as a resonant zero-bias conductance peak [17][18][19][20][21][22][23][24][25][26][27]. Additionally, a three-terminal setup allows to probe nonlocal conductances, which can provide information about the bulk topology and the BCS charge of bound states [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, ZBCPs in local measurements are sensitive to the details of couplings, and so ought to be less robust with varying parameters and disorder. Experiments that simultaneously detect both local and bulk properties, such as non-local conductance, will help resolve this matter [22][23][24][25][26].…”
mentioning
confidence: 99%